Analyzing the Trade-offs Between Credit Risk Management and Profit Maximization in Nepalese Development Banks - Sapkota, Raju (New Journey, 2024)
Effective credit risk management helps mitigate potential drawbacks and enhances the financial performance of development banks. This, in turn, leads to rewarding outcomes for both employees and shareholders, acknowledging their contributions and investments. Credit risk management serves as a crucial predictor of a bank's profitability. Therefore, it significantly influences the financial performance of the bank. The main objective of the study is analyzed the relationship between credit risk management and profitability of Nepalese development banks. Data from a sample of 8 national level development banks operating in the Nepali economy between 2013 to 2023 were collected and analyzed using various statistical methods such as mean, standard deviation, correlation, and regression analysis. Correlation and Regression analysis model of panel data analysis was the primary analytical tool used. In the model specification, Return on assets (ROA) served as the indicator of bank profitability, while indicators of credit risk management included credit to deposit ratio (CDR), Non-performing loan ratio (NPLR), Capital adequacy ratio (CAR), liquidity ratio (LR) and Interest rate spread (IRS). Utilizing data from a sample of development banks, the analysis reveals that the Non-Performing Loan Ratio (NPLR) and Liquidity Ratio (LR) exhibit significant effects on ROA, with associated p-values of 0.00 and 0.04, respectively. Conversely, the Credit to Deposit Ratio (CDR), Capital Adequacy Ratio (CAR), and Interest Rate Spread (IRS) do not significantly influence ROA, as indicated by their p-values exceeding the threshold of 0.05. The overall regression model is statistically significant (F-value of 6.63, p-value of .000), indicating its ability to explain a substantial portion of the variance in ROA. Among the predictors, only the Interest Rate Spread (IRS) demonstrates a positive impact on ROA, while Credit Default Rate (CDR), Non-Performing Loan Ratio (NPLR), Capital Adequacy Ratio (CAR), and Loan-to-Deposit Ratio (LR) have negative effects on ROA. The findings suggest that maintaining lower levels of credit defaults and non-performing loans, along with higher liquidity ratios, may positively influence ROA. However, further research is warranted to delve into the underlying mechanisms and guide strategic decision-making within the banking industry.